Angioscopy - Lovell, Marge; Harris, Kenneth (Operating Room Nurses Association of Canada Journal, 1991)
Over the past three to four decades vascular surgery has experienced increasing interest and rapid growth.This surgical speciality continues to show an annual increase in the number of procedures performed,and demonstrates increasing use of innovative technology. The author explains how the angioscope has emerged as a potentially powerful diagnostic tool for today's vascular surgeon. Its implications, complications and the post operative nursing care for the patient undergoing angioscopy will be discussed.